The Asymmetric Effects of Monetary Policy on Job Creation and Destruction - Garibaldi, Pietro (IMF Working Papers; Working Paper ;, 1997)
This paper presents theory and evidence on the asymmetric effects of monetary policy on job creation and job destruction. First, it solves a dynamic matching model and it shows how interest rate changes result in an asymmetric response of job creation and destruction. Second, it looks at how changes in the federal fund rate affect gross job flows in the U.S. manufacturing industry, and it finds evidence of asymmetry. Tight policy increases job destruction and reduces net employment changes. Conversely, easy policy appears ineffective in stimulating job creation.